FAKTOR YANG MENYEBABKAN MASYARAKAT TIDAK MENGGUNAKAN HAK PILIHNYA DALAM PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR TAHUN 2013 DI TPS 5 RT 4 RW 1 KELURAHAN TUAH KARYA KECAMATAN TAMPAN - Putra, Rona Desmara; Marnelly, T. Romi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Lately, most of the people of the city of Pekanbaru many who opted for abstention or abstain from voting in the democratic party of the people, due to the weakened and low antusiasi society to the General Election. In addition to the above problems finding the low level of community participation has also become a serious problem that occurs in each of the Sub-District of the election of the Governor and Deputy Governor of the city of Pekanbaru years 2013. Because of that conducted a study entitled